2021
DOI: 10.1108/ijes-09-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

The types and effects of feedback received by emergency ambulance staff: protocol for a systematic mixed studies review with narrative synthesis

Abstract: PurposeThe primary aim of this systematic review is to identify, describe and synthesise the published literature on the types and effects of feedback received by emergency ambulance staff. The secondary aim will be to describe the mechanisms and moderators of the effects of prehospital feedback in an organisational context.Design/methodology/approachThe application and effects of feedback for healthcare professionals, to support improved practice, is well researched within the wider healthcare domain. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The study was defined as a ‘systematic mixed studies review’, as preliminary searches identified important quantitative, qualitative and mixed-methods studies of relevance to the review aims 13. The review was registered on PROSPERO (CRD42020162600) and the protocol published a priori 14…”
Section: Methodsmentioning
confidence: 99%
“…The study was defined as a ‘systematic mixed studies review’, as preliminary searches identified important quantitative, qualitative and mixed-methods studies of relevance to the review aims 13. The review was registered on PROSPERO (CRD42020162600) and the protocol published a priori 14…”
Section: Methodsmentioning
confidence: 99%